PENGARUH PENERAPAN TEORI FLAVELL TERHADAP KEMAMPUAN BERHITUNG ANAK KELOMPOK B DI TK NEGERI PEMBINA INDRALAYA SELATAN - Marlina marlina; Syafdaningsih syafar; Rukiyah Rukiyah (FKIP Universitas sriwijaya, 2017)
The influence of the application of the theory flavell of the ability of counting on child which was carried out on group B in TK Negeri Pembina Indralaya Selatan with the kind of research pre-eksperimental with the design one shoot case study. Technique the sample used is purposive sampling with consideration of count remain low class B2. Sample were 20 children. Treatment done as many as five times and each performed posttest. Posttest used a test of what consisting of 5 indicators.A value on every posttest totaled divided 5 obtained the average score 76,75. As data was hypothesized was the data on that is in class a lower limit intervals to a category bsh namely 63. From our analysis data is collected t value = 4,11 ? t table value = 1.73 with the economic situation of significant 5 percent and dk ( 19 ) so that concluded is the theory Flavell of the ability of count children group B in TK Negeri Pembina Indralaya Selatan. This can be seen in every indicator four of the five indicators dominant appear that is connecting the number of pictures by in number , rank the number of , distinguish the concept of many little, counting the results of reduction. While an indicator that less appear counting the results of a sum. Is expected in learning next was even more many trained indicators counting the results of a sum according to the theory Flavell with to the media to learning.